Optimal clone identifier for genomic shotgun libraries: OC Identifier tool - Cantão, M. E. [UNESP]; Ferreira, J. E.; Lemos, E. G. M. [UNESP] (My University, 2007)
In DNA microarray experiments, the gene fragments that are spotted on the slides are usually obtained by the synthesis of specific oligonucleotides that are able to amplify genes through PCR. Shotgun library sequences are an alternative to synthesis of primers for the study of each gene in the genome. The possibility of putting thousands of gene sequences into a single slide allows the use of shotgun clones in order to proceed with microarray analysis without a completely sequenced genome. We developed an OC Identifier tool (optimal clone identifier for genomic shotgun libraries) for the identification of unique genes in shotgun libraries based on a partially sequenced genome; this allows simultaneous use of clones in projects such as transcriptome and phylogeny studies, using comparative genomic hybridization and genome assembly. The OC Identifier tool allows comparative genome analysis, biological databases, query language in relational databases, and provides bioinformatics tools to identify clones that contain unique genes as alternatives to primer synthesis. The OC Identifier allows analysis of clones during the sequencing phase, making it possible to select genes of interest for construction of a DNA microarray. ©FUNPEC-RP.
Keywords: Bioinformatics tool; Comparative genomic hybridization; DNA microarray; Gene expression; Genomic shotgun libraries; Optimal clones; DNA fragment; oligonucleotide; transcriptome; bioinformatics; conference paper; factual database; gene sequence; genetic algorithm; genome; genome analysis; molecular cloning; molecular library; molecular phylogeny; nucleotide metabolism; open reading frame; polymerase chain reaction; sequence analysis; Clone Cells; Cloning, Molecular; Computational Biology; Genome, Bacterial; Genomic Library; Open Reading Frames; Software